Application of Problem-Based Learning Model to Improve Mathematical Problem-Solving Ability of Class VII-B Students of MTs PP Nurul Huda Lubuk Batu Jaya - Tri Avianti; Putri Yuanita; Sakur (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This classroom action research aims to improve the problem-solving process and students' mathematical problem-solving skills by applying the Problem Based Learning model. The subjects in this study were class VII-B students of MTs PP Nurul Huda Lubuk Batu Jaya in the even semester of the 2021/2022 school year, totaling 24 students. This study consisted of two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research instruments used were learning devices and data collection instruments. Learning tools consist of a syllabus, lesson plan (RPP), and student activity sheets (LAS), while the data collection instruments used are observation sheets and KPMM tests. Data from the observation sheet shows that the learning process has improved from cycle I to cycle II. The average KPMM score of students in the first cycle was 68.61, increasing to 86.36 in the second cycle. Based on the results obtained, it can be concluded that the Problem Based Learning model can improve the learning process and the mathematical problem-solving abilities of class VII-B MTs PP Nurul Huda Lubuk Batu Jaya students in the even semester of the 2019/2020 school year.